Pengaruh Pelayanan, Lokasi, Pengetahuan, dan Sosial Terhadap Keputusan Menabung di Ponorogo - AUDINA PUTRIBASUTAMI, CINDHY; SISTA PARAMITA, R.A. (Jurnal Ilmu Manajemen (JIM), 2018)
Nowdays, people believe to save money in banking. Before deciding to merge in a bank, people consider the factors and benefits if they are choosing the bank. The main purpose of this research is to test the influence of service, location, knowledge, and social of saving decision people in Ponorogo at Conventional Bank and Sharia Bank, so in this research there are two models that will explain the effect of saving in Conventional Bank and Sharia Bank. The type of research is quantitative research by using purposive sampling method and obtained 220 respondents. The objects of this research were customers in conventional banks and sharia banks. The data obtained by spreading questioners with 20 items of the statement to customer. The technique of data analysis using multiple linear regression. Research result, service, knowledge, and social are influence to saving decision in Ponorogo at the Conventional Bank. The most dominating variable is service, so if the bank provides good service then the decision to save will increase. Location variable has not infuence because customers can make transaction via ATM or Mobile Banking that has been provide by the bank, so customers do not need come to the bank. In Sharia Bank, Research result, service, location, knowledge, and social are influence to saving decision in Ponorogo. The most dominating variable is social, so it is necessary to socialize for public so that people willing to save in Sharia Bank. Keywords: saving decision, Conventional Bank, Sharia Bank